IMPLEMENTASI PENEGAKAN KETENTUAN PIDANA TERHADAP PELANGGARAN HAK KEKAYAAN INTELEKTUAL REGIM HAK CIPTA - Indra Ariska, Dudung (Yustitia, 2018)
Indonesia as an archipelago has a very rich diversity of cultural arts. This is in line with the diversity of ethnicity, trabs and religion as a whole is a national potential which needs to be protected. After the enactment of Law No. 19 of 2002, the creators in the field of literature and science received legal protection so that it is no longer turned off the creativity of its employees. Normatively, if there is piracy, the sanctions imposed are very severe, namely a seven-year prison sentence and / or a maximum fine of IDR 5,000,000,000.00 (five billion rupiah). In fact, piracy is still ongoing. The current development of piracy is due to law enforcement carried out by law enforcement officers in this case the police are not carried out thoroughly and thoroughly, or in other words run half-heartedly so that there is no single case of piracy in the film sector that can be used as jurisprudence